P3/O3 Integrated Layered Oxide as High‐Power and Long‐Life Cathode toward Na‐Ion Batteries - Zhang, Si‐Yuan; Guo, Yu‐Jie; Zhou, Ya‐Nan; Zhang, Xu‐Dong; Niu, Yu‐Bin; Wang, En‐Hui; Huang, Lin‐Bo; An, Peng‐Fei; Zhang, Jing; Yang, Xin‐An; Yin, Ya‐Xia; Xu, Sailong; et al. (Small (Weinheim an der Bergstrasse, Germany), 2021)
Low‐cost and stable sodium‐layered oxides (such as P2‐ and O3‐phases) are suggested as highly promising cathode materials for Na‐ion batteries (NIBs). Biphasic hybridization, mainly involving P2/O3 and P2/P3 biphases, is typically used to boost their electrochemical performances. Herein, a P3/O3 intergrown layered oxide (Na2/3Ni1/3Mn1/3Ti1/3O2) as high‐rate and long‐life cathode for NIBs via tuning the amounts of Ti substitution in Na2/3Ni1/3Mn2/3−xTixO2 (x = 0, 1/6, 1/3, 2/3) is demonstrated. The X‐ray diffraction (XRD) Rietveld refinement and aberration‐corrected scanning transmission electron microscopy show the co‐existence of P3 and O3 phases, and density functional theory calculation corroborates the appearance of the anomalous O3 phase at the Ti substitution amount of 1/3. The P3/O3 biphasic cathode delivers an unexpected rate capability (≈88.7% of the initial capacity at a high rate of 5 C) and cycling stability (≈68.7% capacity retention after 2000 cycles at 1 C), superior to those of the sing phases P3‐Na2/3Ni1/3Mn2/3O2, P3‐Na2/3Ni1/3Mn1/2Ti1/6O2, and O3‐Na2/3Ni1/3Ti2/3O2. The highly reversible structural evolution of the P3/O3 integrated cathode observed by ex situ XRD, ex situ X‐ray absorption spectra, and the rapid Na+ diffusion kinetics, underpin the enhancement. These results show the important role of P3/O3 biphasic hybridization in designing and engineering layered oxide cathodes for NIBs. P3/O3 biphasic Na2/3Ni1/3Mn1/3Ti1/3O2 cathode material is prepared for Na‐ion batteries by tuning the Ti amounts. This P3/O3 intergrown cathode delivers superior rate capability and cycling stability to those of the pristine P3 and O3 phases, which are underpinned by the observed highly reversible structural transition of P3/O3 biphase and the rapid Na+ diffusion kinetics.